80.6k views
4 votes
(6x-5)+(-7x+2)
and
(6x-5)-(-7x+2)
Need work

User Sherryann
by
5.0k points

2 Answers

4 votes

☆Answer :

  • A)

6x - 5 + (-7x + 2) = ...

= 6x - 5 - 7x + 2

= (6x - 7x) + (-5 - 2)

= -x - 7


\:

  • B)

6x - 5 - (-7x + 2) = ...

= 6x - 5 + 7x + 2

= (6x + 7x) + (-5 + 2)

= 13x - 3

User Branislav Lazic
by
5.2k points
2 votes

Answer:(6x-5)+(-7x+2)

1 Remove parentheses.

6x-5-7x+2

2 Collect like terms.

(6x-7x)+(-5+2)

3 Simplify.

-x-3

_____________________________

1 Remove parentheses.

6x-5+7x-2

6x−5+7x−2

2 Collect like terms.

(6x+7x)+(-5-2)

3 Simplify.

13x-7

Hope this helps

-Tobie the dog <3

User Studentbi
by
4.6k points